Resourceful mobilizing for resource mobilization - Place, Frank (International Food Policy Research Institute, 2017)
Presented by Frank Place (IFPRI), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017